Criterion-Related Validity and Reliability of the Front Plank Test in Adults: The ADULT-FIT Project - Ángela Rodríguez-Perea; Pedro Aragón-Aragón; Magdalena Cuenca-García; Carolina Cruz-León; Maximiliano Torres-Banduc; Sandra Sánchez-Parente; José Castro-Piñero (Applied Sciences)
Background: the validity and reliability of the front plank test (FPT) have been studied in young adults but not in adults aged 34 to 60 years. The aim of this study was to analyze the criterion-related validity and reliability of the front plank test (FPT) for evaluating trunk musculature in adults according to sex and age groups. Methods: a repeated measures design was used to study the reliability of the FPT. A total of 84 adults aged 18–62 years performed trunk muscular force tests and the FPT. Criterion-related validity was assessed using repeated measures ANOVA. Reliability was examined by ICC, error measurements, and Bland–Altman analysis across sex and age groups. Results: significant differences in the activation of the rectus abdominis and external oblique muscles were found compared with the erector spinae and multifidus muscles (p < 0.001). No correlations were found between FPT time and physical activity or rate of perceived exertion at the end (p > 0.05). Low and moderate correlations were found with body fat percentage, trunk fat mass percentage, and external oblique, regardless of sex and age groups (p < 0.05). Extremely high reliability was found regardless of sex and age groups (ICC > 0.98), with low error measurements (RMSE = 11.93–18.73; %CV = 4.91–6.33; SEE = 11.45–16.84). MDC90 values indicated no real change between T1 and T2. Conclusion: FPT is a valid and reliable test for assessing trunk musculature in adults regardless of sex and age groups.